2007
DOI: 10.1074/jbc.m702504200
|View full text |Cite
|
Sign up to set email alerts
|

RAET1E2, a Soluble Isoform of the UL16-binding Protein RAET1E Produced by Tumor Cells, Inhibits NKG2D-mediated NK Cytotoxicity

Abstract: UL16-binding proteins (ULBPs 14 -21). ULBP gene family consists of 10 members, six of which encode potentially functional glycoproteins that are located near the tip of its long arm at q24.2-q25.3, close to the human equivalent of the mouse H2-linked t-complex. This subchromosomal region is similar to a segment of mouse chromosome 10 harboring the orthologous MHC class I-related retinoic acid early transcript loci, Raet1a-d (22). Among them, ULBP1, ULBP2, ULBP3, and RAET1L are linked to membrane through a glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…In gastrointestinal tumors, but not always in breast and lung cancers, NKG2D-L levels are systematically increased compared with adjacent normal tissues (31). We showed that NKG2D-L is involved in most tumor cell lines killing, but we and others also showed that soluble MICA/B is a major mechanism inhibiting NK cells activation against tumor cells (32,33). sMICA expression is even considered as a poor prognosis factor in breast cancer (34).…”
Section: Discussionmentioning
confidence: 99%
“…In gastrointestinal tumors, but not always in breast and lung cancers, NKG2D-L levels are systematically increased compared with adjacent normal tissues (31). We showed that NKG2D-L is involved in most tumor cell lines killing, but we and others also showed that soluble MICA/B is a major mechanism inhibiting NK cells activation against tumor cells (32,33). sMICA expression is even considered as a poor prognosis factor in breast cancer (34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, soluble forms of ULBP2 and ULBP4 (also named as RAET1E2 or LETAL (lymphocyte effector cell toxicity activating ligand)) have been described (Salih et al, 2006;Waldhauer and Steinle, 2006;Cao et al, 2007). However, engagement of the NKG2D receptor by soluble ligands does not necessarily lead to the downregulation of cell surface expression of NKG2D .…”
Section: Nkg2d In Antitumor Responsesmentioning
confidence: 99%
“…UL-16 binding protein (ULBP) is a novel ligand for NKG2D receptor in humans (15). We found that RAET1E2, a soluble isoform of the UL16-binding protein RAET1E produced by tumor cells, inhibits NKG2D-mediated NK cytotoxicity (16). Because of the sequence and structure similarity of the extracellular domains between MICA and ULBPs, ULBPs are also considered as antigens for V␦1 ␥␦T cells (17).…”
mentioning
confidence: 99%